1956
DOI: 10.1121/1.1908622
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Human Skull to Mechanical Vibrations

Abstract: Measurements of the mechanical impedance and of the vibration pattern of the human skull are described. In the frequency range from 200 to 1600 cps the skull was excited to vibrations by means of an electrodynamically actuated piston with small contact area. Data were obtained from living subjects, a dry skull preparation, and a human cadaver. The modulus of elasticity of skull bone, calculated from the resonance frequency of the skull, was found consistent with the value obtained by static methods. The propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

1958
1958
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 1 publication
3
31
1
Order By: Relevance
“…Several investigations of the skull point impedance have been reported in the literature, both with and without the skin covering the skull bone, using living and cadaver heads as well as severed dry skulls ͑Corliss and Coidan, 1955;Franke, 1956;Stalnaker and Folge, 1971;Gurdjian et al, 1970;Flottorp and Solberg, 1976;Smith and Suggs, 1976;Håkansson et al, 1986͒. Of these, the most thorough investigation is Håkansson et al ͑1986͒, where the mechanical point impedance at an osseointegrated titanium implant, as well as at the skin in the parietal bone ͑about 55 mm behind the ear canal entrance͒, was investigated in seven living humans.…”
Section: A Mechanical Point Impedance Of the Skullmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations of the skull point impedance have been reported in the literature, both with and without the skin covering the skull bone, using living and cadaver heads as well as severed dry skulls ͑Corliss and Coidan, 1955;Franke, 1956;Stalnaker and Folge, 1971;Gurdjian et al, 1970;Flottorp and Solberg, 1976;Smith and Suggs, 1976;Håkansson et al, 1986͒. Of these, the most thorough investigation is Håkansson et al ͑1986͒, where the mechanical point impedance at an osseointegrated titanium implant, as well as at the skin in the parietal bone ͑about 55 mm behind the ear canal entrance͒, was investigated in seven living humans.…”
Section: A Mechanical Point Impedance Of the Skullmentioning
confidence: 99%
“…Also, the vibration of a large part of the human cranial vault has been visualized with holographic interferometry ͑Ogura et Hoyer and Dör-heide, 1983;Dorheide and Hoyer, 1984͒. Other investigations have aimed at estimating the propagation velocity and type of wave transmission in the human skull ͑von Békésy, 1948;Zwislocki, 1953;Franke, 1956;Tonndorf and Jahn, 1981͒. Theoretical approaches to estimate the skull response during vibration stimulation have also been used. For this, thin-shell theories of spheres with fluid loading were used to achieve analytical results, or finite element analysis was used to obtain the vibration pattern ͑Advani and Lee, 1970;Hickling and Wenner, 1973;Khalil and Hubbard, 1977;Charalambopoulos et al, 1998;Young, 2002.…”
Section: Introductionmentioning
confidence: 98%
“…Von Bekesy (1948) Experimental study on human skull. Skull 1800 Franke (1956) Experimental study on a dry human skull with the use of vibrating piston.…”
Section: Comparison Of Fundamental Frequencymentioning
confidence: 99%
“…Von Bekesy (1948) investigated the vibration response of a cadaver skull in an acoustic field and reported that the first resonant frequency of the skull to be 1800 Hz. The experimental modal study, performed by Franke (1956) on both an empty dry human skull and the same skull filled with gelatin, found that the lowest resonant frequencies were 800 and 500 Hz, respectively. Both Hodgson et al (1967) and Gurdjian et al (1970) reported that the resonant frequency of a cadaver head in their mechanical impedance analysis was approximately 300 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the velocity of sound traveling through the skull vary widely depending upon the estimation method used. Franke (1956) applied a signal to the human forehead and measured the delay between a pair of points. His results were dependent on frequency: the velocity of lower frequency sounds was estimated at 80 m/s, while higher frequencies traveled at up to 300 m/s.…”
Section: Sumariomentioning
confidence: 99%